Bacteriological Profile and Drug Susceptibility in Mucosal type Chronic Suppurative Otitis Media - Maharjan, Rajesh; Sigdel, Brihaspati; Nepali, Rajendra (Journal of Nepal Health Research Council, 2023)
Background: In Chronic Suppurative Otitis Media, mucosal type, most common organisms are Pseudomonas aeruginosa and Proteus species (P. mirabilis and P. vulgaris). It is important to prescribe culture-directed antibiotics to prevent resistance. This study was conducted to determine the bacteriological profile and drug susceptibility in patient with chronic suppurative otitis media. Methods: This is a hospital-based descriptive study done at Gandaki Medical College, Pokhara, Nepal from July 2019 to June 2020. Under aseptic condition, the swab specimens were obtained from patients with history of ear discharge of >12 weeks duration and findings central perforation of the tympanic membrane. The sample was labeled and immediately transferred to the microbiology lab for culture/sensitivity test according to the guidelines of the Clinical and Laboratory Standards Institute. Results: Out of total 127 patients, 48 (37.8%) were male and 79 (62.2%) were female. One hundred and seven samples (84.3%) had positive culture while 20 samples (15.7%) had no growth. Staphylococcus aureus (43%), was the most common isolate followed by Pseudomonas aeruginosa (23.4%), Proteus mirabilis (9.3%), and Escherichia coli (8.4%). All the organisms isolated were 100% sensitive to imipenem followed by 96.2% sensitive to gentamicin and 95.3% to amikacin. Conclusions: Staphylococcus aureus (43%) was the most predominant isolate followed by Pseudomonas aeruginosa (23.4%), Proteus mirabilis (9.3%), and Escherichia coli (8.4%). Imipenem was the most sensitive antibiotic (100%) followed by gentamicin (96.2%), amikacin (95.3%), and ofloxacin (88.78%). Keywords: Antibiotic susceptibility; bacteriology; chronic suppurative otitis media